Directions and ways of executing judo throws during judo contests as a control criterion of an individual`s training versatility - Adam, M.; Laskowski, R.; Smaruj, M. (Baltic Journal of Health and Physical Activity, 2012)
Background: Symmetry of movement actions in sport is considered as an element of versatility which enlarges an individual`s technical and tactical capacity. Asymmetry usually limits this capacity and may also lead to overstrains of one side of the body and cause an injury. The research is done on health aspects and practical improvement in sport contest. Up-to-date research on judo contest effectiveness has been aimed at the ability of throwing into various directions. There is no material and data as compared to the directions of throwing and effective directions of the opponent`s attack. The purpose of this research was to find relationships between the directions of the executed throws and the side of competitors` bodies used while throwing.